2017
DOI: 10.1111/ropr.12253
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and Morality Policy in Western Democracies

Abstract: This article investigates whether different political institutions such as executives, legislatures, parties, party systems, judiciaries, decentralization, constitutionalism, and referendums across 24 Western democracies are venues for debate across five individual morality policies. Using data since 1945, the article compares three theories of morality policy-(1) Policy Type leading to different institutional venues; (2) Two Worlds of religious/secular party systems; and (3) U.S./European exceptionalism. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…While critics have pointed out important deviant cases that may require the inclusion of additional variables and a shift to a more dynamic perspective (Hurka et al, 2018), EGPL’s parsimonious approach explains much of the variation in morality policymaking in Europe (Studlar and Cagossi, 2017). What is lacking, however, is any attempt to establish the micro-foundations of the two-worlds framework in European mass publics.…”
Section: Introductionmentioning
confidence: 99%
“…While critics have pointed out important deviant cases that may require the inclusion of additional variables and a shift to a more dynamic perspective (Hurka et al, 2018), EGPL’s parsimonious approach explains much of the variation in morality policymaking in Europe (Studlar and Cagossi, 2017). What is lacking, however, is any attempt to establish the micro-foundations of the two-worlds framework in European mass publics.…”
Section: Introductionmentioning
confidence: 99%
“…This simple religious/secular distinction captures much of the variation in morality policy making in Europe (Studlar and Cagossi 2018). Prima facie, the framework also fits the case of PGD remarkably well, as both the most permissive (Belgium) and the most restrictive regimes are found in the religious world.…”
Section: Theoretical Frameworkmentioning
confidence: 70%
“…Attempts to test these hypotheses have yielded mixed results. Whereas Studlar et al (2013) found evidence for the policy typology theory, Studlar and Cagossi (2018) found considerable variation between countries and policy issues with regard to the procedural elements of morality policies.…”
Section: Morality Policies As Engendering a Specific Type Of Politicsmentioning
confidence: 98%
“…Regardless of whether it is seen as regulatory or redistributive, many authors argue that morality policies exhibit their own type of politics. This politics is characterized by large-scale public and interest group involvement, divisive party and legislative politics, the involvement of multiple institutions, lack of executive leadership, and a strong impact of federalism on outcomes (Studlar and Burns, 2015; Studlar and Cagossi, 2018). Attempts to test these hypotheses have yielded mixed results.…”
Section: Morality Policies As Engendering a Specific Type Of Politicsmentioning
confidence: 99%